Impact of clean intermittent catheterization on quality of life of patients with neurogenic lower urinary tract dysfunction due to radical hysterectomy: A cross‐sectional study - Sekido, Noritoshi; Takaoka, Ei‐ichiro; Nishiyama, Hiroyuki; Ochi, Hiroyuki; Satoh, Toyomi (Lower urinary tract symptoms, 2021)
Aims We investigated the quality of life (QOL) of a homogenous group of ambulant patients with neurogenic lower urinary tract dysfunction without significant comorbidities to elucidate the impact of clean intermittent catheterization (CIC) on QOL. Methods The subjects were 71 female patients who underwent radical hysterectomy (RH) without recurrent disease. QOL was cross‐sectionally measured with the Short‐Form 36‐Item Health Survey (SF‐36) and King's Health Questionnaire (KHQ). We divided urinary management into spontaneous voiding (SV) and CIC as well as postoperative elapsed time into the entire period, less than 24 months (<24 months) and 24 months or more (≥24 months). Results Patients with CIC showed significantly poorer QOL than patients with SV in some subscale/domain scores on SF‐36 and KHQ for the entire period as well as <24 months after RH. In contrast, significant differences were not revealed between scores on both measures of patients with CIC and SV ≥24 months after RH. Moreover, in patients with CIC ≥24 months, some subscale/domain scores on both measures were significantly better than in those with <24 months. Norm‐based scoring of SF‐36 revealed that all subscales of patients with CIC <24 months were below the average score of healthy Japanese people, while only four subscales of those ≥24 months remained below the average. Conclusions QOL in patients with CIC was worse than in patients with SV in the short term, but similar in the long term, which suggests that QOL probably might improve with time in patients with CIC.